Campos de conflitividade política e movimentos sociais no Equador da Revolução Cidadã - Ramírez Gallegos, Franklin (2015)
The aim of this article is to analyze the configuration of diverse "political conflictivity fields" emerged during the governmental cycle known as "Citizen Revolution" started in 2007. This government, headed by Rafael Correa, triggered a political change process in the midst of a deep legitimacy crisis of political representation and of withdrawal of social movements. The new public agenda, outlined during the Constituent Assembly, prompts a set of contentious episodes that reveal the capacity of organized collective action, despite its weakness, to construct large public problems. In this sense, the paper explores three political conflictivity fields related to specific social problems raised at grassroots level: the deficit of political recognition, the legitimacy of the social representation into the State, and the links between buen vivir (good living) and development.